2017
DOI: 10.1038/s41598-017-02049-9
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity induces inhibition of osteoblastic differentiation and mineralization through abrogating primary cilia

Abstract: It is well documented that microgravity in space environment leads to bone loss in astronauts. These physiological changes have also been validated by human and animal studies and modeled in cell-based analogs. However, the underlying mechanisms are elusive. In the current study, we identified a novel phenomenon that primary cilia (key sensors and functioning organelles) of rat calvarial osteoblasts (ROBs) gradually shrank and disappeared almost completely after exposure to simulated microgravity generated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 53 publications
6
51
0
Order By: Relevance
“…While these findings collectively suggest that cellular tension is important for mediating cell fate decisions, studies by Sen et al recently showed cellular tension transmitted through the actin cytoskeleton (and subsequent bone formation in vitro and in vivo) was not the sole determining factor of deciding cell fate but that the specific control of gene expression was primarily dependent on intranuclear actin transport [24]. In other studies by Shi et al and Chen et al, CytoD has been shown to have reduced the viability and osteogenic differentiation of calvarial osteoblasts and tendon stem cells, in vitro [39,40]. These inhibitory responses could be attributed to cell shape status and confluency conditions before CytoD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While these findings collectively suggest that cellular tension is important for mediating cell fate decisions, studies by Sen et al recently showed cellular tension transmitted through the actin cytoskeleton (and subsequent bone formation in vitro and in vivo) was not the sole determining factor of deciding cell fate but that the specific control of gene expression was primarily dependent on intranuclear actin transport [24]. In other studies by Shi et al and Chen et al, CytoD has been shown to have reduced the viability and osteogenic differentiation of calvarial osteoblasts and tendon stem cells, in vitro [39,40]. These inhibitory responses could be attributed to cell shape status and confluency conditions before CytoD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these events result in bone loss as well as reduced bone mechanical properties in rodents [49][50][51][52] . In addition, exposure to microgravity in mice adversely affects osteoprogenitors 53,54 . The bone marrow niche contains osteoblast progenitors cells 4 and it has been shown that exposure to microgravity alters the cells proliferation capacity and impairs their ability to produce extracellular matrix, in turn inhibiting the maturation of the bone matrix.…”
mentioning
confidence: 99%
“…The bone marrow niche contains osteoblast progenitors cells 4 and it has been shown that exposure to microgravity alters the cells proliferation capacity and impairs their ability to produce extracellular matrix, in turn inhibiting the maturation of the bone matrix. Thus, the ability to maintain bone homeostasis is diminished 16,[54][55][56] .…”
mentioning
confidence: 99%
“…A recent study reported that the microgravity-induced effect on syncytin-A expression stimulated osteoclast formation independently of receptor activation of nuclear factor-kappa B ligand (RANKL), a crucial bone resorption factor, in mouse monocytic RAW264.7 cells [34]. Regarding osteoblasts, microgravity suppresses cell metabolism by impairing the cell mitochondrial energy state in human osteoblasts; further, it represses rat osteoblast differentiation by affecting primary cilia, which partly sense mechanical stress [35,36]. Moreover, spaceflight has been reported to result in enhanced bone resorption by inducing osteocyte death and the subsequent bone mass deterioration and microstructure in mice [37].…”
Section: Muscles and Bonesmentioning
confidence: 99%